A critical appraisal of the concept of climate migration. Issue 3 (16th February 2022) - Lauria, Giovanna
Abstract: This article analyses international legal scholarship and policy developments on the climate-migration nexus through the lens of the relationship between international law and crisis. It argues that legal and policy debates on climate-related mobility reflect an oscillation between two dimensions associated with crisis narrative: catalyst and decoy.